ACQUISITION OF PHONEMES FROM PARENTS' SPEECH ACT TO CHILDREN AGED 3-5 YEARS IN MAMOLO VILLAGE, NUNUKAN REGENCY - Ulinsa, Ulinsa; Rahmat, Wahyudi; Noviana, Manda Eva (ppjbsip, 2021)
This research is motivated by an interest in the process of language acquisition in children, especially at the phonological level, namely the acquisition of phonemes aged 3-4 years. This research study uses psycholinguistics and pragmatics. This study describes how acquiring phonemes for children aged 3-4 years in Mamolo village, Nunukan district is described in source from speech act the parents. The type of research used is qualitative research, namely by observing and taking notes. Based on the research findings, it is concluded that children aged 3-4 years have difficulty pronouncing consonant phonemes. The object has not mastered the phonemes /x/ and /z/ and has not distinguished the sounds /p/, /f/, and /v/. As well as the release of sounds such as the phoneme /s/ becomes /c/ in [pain] becomes [cakit].